MENINGKATKAN KEMAMPUAN PENYESUAIAN DIRI SISWA MELALUI TEKNIK COGNITIVE RESTRUCTURING PADA KELAS X TKR 1 SMK NEGERI 7 SEMARANG TAHUN 2012/2013 - Windaniati Windaniati (Universitas Negeri Semarang, 2015)
SMK Negeri 7 Semarang has 64 classes consist of 9 departments. The transition period of learning system from SMP to SMK creates various students’ adaptation ability. Based on the psychological scales, there were 7 of 36 students (20%) of Class X TKR 1 who had low or less adaptation ability. The objectives of this reaserach are: (1). to know the effectivity of the Cognitive Restructuring Technique in increasing students’ adaptation ability of Class X TKR 1 SMK Negeri 7 Semarang; (2). To know the significancy of the increasing of the students’ adaptation ability through Cognitive Restructuring Technique for students of Class X TKR 1 SMK Negeri 7 Semarang. This is a Guidance Counseling Action Research. The subjects were 10 students of Class TKR 1. Data were collected through observation, psychological scales, and interviews. The quantitative and qualitative data were analized descriptively and comparatively, by comparing the conditions in precycle, cycle 1, and cycle 2. The result showed that (1). based on the observation, the indicator of adaptation and good category of restructuring cognitive in cycle 1 increased 62%, from 15% to 77%, subjects with enough category decreased from 56% to 18%, whereas subjects with less category decreased from 29% in cycle 1 to 5% in cycle 2; (2). based on the measurement of adaptation ability through psychological scales of adaptation, high category of adaptation increased from)% in precycle and cycle 1 to 50% in cycle 2, medium category increased from 30% in precycle to 80% in cycle 1, and decreased to 50% in cycle 2. The decreasing happened because in cycle 2 there were some subjects belonged to the high category. Subjects in less category were 50%, they decreased to 20% in cycle 1 and 0% in cycle 2. Subjects in low category were 20% in precycle, and they decreased to in cycle 1; (3). the average scores of the students’ adaptsation ability increased 26.40% from the early condition to cycle 1.Students’ adaption ability increased 11.65% from cycle 1 to cycle 2 after the imrpovement in cycle 2. Thus, in average, the subjects in this research could increased to 41.12%. Restructuring Cognitive could increase the students’ peer relations and productivity and could decrease students’ dependency, hostility, and withdrawal.